Engagement in international entrepreneurship: Interactive effects of resource-based factors and institutional environments - Tianchen Li (Journal of Global Entrepreneurship Research, 2019)
Purpose: Integrating the resource-based view and institutional approach, this study aims to examine how resource-based factors and formal and informal institutional context interact in influencing the international engagement. Design/methodology/approach: Based on the data from the Global Entrepreneurship Monitor surveys, this paper performs a multilevel estimation approach in which cross-level (random effects) moderation analysis is applied. Findings: This paper offers new insights into the internationalisation by ascertaining the primary role of resource-based factors in influencing internationalisation. In addition, it reveals the differential contingent values of formal and informal institutions in regard to the relationship between resource-based characteristics and internationalisation. Practical implications: The research findings reveal the importance of the countryspecific institutional system to drive early stage entrepreneurs' intention to go international. In addition, the significant impacts of formal and informal institutions call upon policy-makers to improve institutional environments (e.g. government policies, governmental programmes, entrepreneurial finance, market openness, commercial and professional infrastructure, intellectual property rights, etc.). Research originality: This research indicates that the degree of internationalization increases when entrepreneurs possess the necessary resources and under suitable formal and informal institutional environments.
Keywords: 650; Internationalisation; Resource-based view; Institutional theory; Global Entrepreneurship Monitor